Rancang Bangun Aplikasi Ensiklopedia Kesehatan Berbasis Android - Ferdiyani Haris (Jurnal Sains Komputer dan Teknologi Informasi, 2018)
In the world of health, many health terms are difficult to understand. The health encyclopedia book is one of the media that presents an explanation of these terms. But in its use, the printed book is less effective and efficient because of limited space and time. So we need a media that explains health terms that are mobile so that they can be used whenever and wherever. This application was designed and implemented for the Android operating system. The system created aims to display definitions and images of health terms. The research method used is the research and development method. While for the development of software systems using the Software Development Life Cycle (SDLC) waterfall software development model. Based on the results of the response to application users conducted with a questionnaire resulting in a value of 88.9% stated very well.